Is stress an important co morbid factor for hypertension among legal professionals - Kannan, L.; P., Praveena (International Journal Of Community Medicine And Public Health, 2018)
Background: Stress is a mental, physical and emotional response to life demands. Long hours of work, client demands, changing laws- creates stress and eventually hypertension among advocates. Well-being of the advocates are being questioned. Hence the main objective of the study is to evaluate the relationship between stress and hypertension among practising advocates. Methods: A cross-sectional study was conducted in a sample of 300 practising advocates at Madurai district court for a period of 1 year by simple random sampling method. Results: Around 133 (44.33%) and 167 (55.66%) of study participants were in level of high stress and low stress respectively. Among high stressed participants, a majority of 113 (84.96%) were found to be hypertensives and among the low stressed participants only 10 (5.98%) were hypertensives. The difference of observation was found to be statistically significant (p=0.0000). Conclusions: In conclusion the study explains that practising advocates with high perceived stress 113 (84.96%) were found to be hypertensives. Stress has a significant association with hypertension. The right way to manage stress is to implement coping strategies.